Outcomes of Medial Collateral Ligament Injuries during Total Knee Arthroplasty - Siqueira, Marcelo B. P.; Haller, Kathryn; Mulder, Andrew; Goldblum, Andrew S.; Klika, Alison K.; Barsoum, Wael K. (The Journal of Knee Surgery, 2016)
Intraoperative medial collateral ligament (MCL) disruption during total knee arthroplasty (TKA) is often managed with either primary repair or use of a constrained implant. A total of 23 patients with an MCL injury during TKA between 2003 and 2009 were compared with 92 matched controls. Of the 23 patients, 10 were treated with an unconstrained implant and primary MCL repair, 8 with constrained implants, 3 with constrained implants and MCL repair, and 2 with unconstrained implants and no MCL repair. After an average 5-year follow-up, patients had lower Knee Society Scores (KSS), 79 versus 87 (p = 0.03), but similar Knee Function Scores (KFS), 68 versus 72 (p = 0.35). The improvement between preoperative and postoperative KSS and KFS did not vary among the two groups (p = 0.88 and p = 0.77, respectively). Postoperative scores did not vary significantly among the four treatment modalities. Conservative treatment can provide satisfactory outcomes and avoid potential complications of increased constraint.
Keywords: total knee arthroplasty; intraoperative medial collateral ligament injury; ligament repair; constrained implants